Implementation of information systems security policies: a survey in small and medium sized enterprises - Lopes, Isabel Maria (2015)
Information has become organizations’ most valuable asset, thus being a potential target to threats intending to explore their vulnerabilities and cause considerable damage. Therefore, there is a need to implement policies regarding information systems security (ISS) in an attempt to reduce the chances of fraud or information loss. Thus, it is important to find the critical success factors to the implementation of a security policy as well as to assess the level of importance of each one of them. This paper contributes to the identification of such factors by presenting the results of a survey regarding information systems security policies in small and medium sized enterprises (SME). We discuss the results in the light of a literature framework and identify future works aiming to enhance information security in organizations.